N-type behavior of ferroelectric-gate carbon nanotube network transistor - Cheah, Jun Wei (2011)
Carbon nanotube field effect transistor has attracted much attention recently and is a promising candidate for next generation nanoelectronics. Here, we report our study on a transistor using single wall carbon nanotube network as the channel and a ferroelectric film as the gate dielectric. The spontaneous polarization of ferroelectric materials offers nonvolatility and controllability of the surface charges. Modulation of >10^2 in the channel conductivity has been observed in the network-based transistor. Voltage pulses are used to control the transistor states; no continuous gate bias is needed. Furthermore, n-type behavior of the network channel is observed, which is attributed to a change in the Schottky barrier at the carbon nanotube-metal interface.